Differences in Levels of Human 1,3β-D-Glucan from Bronchoalveolar Lavage (BAL) Fluid in The Immunocompromised and Immunocompetent Groups Patients with Suspected Lung Cancer - Asih Trimurtini; Ngakan Putu Parsama Putra; Teguh Rahayu Sartono; Harun Al Rasyid (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Invasive candidiasis occurs in immunocompromised individuals as an opportunistic infection in patients with lung cancer. Although culture and histopathology remain the standard diagnosis of fungal infections, other tests are still needed to provide faster results. Human 1,3-β-D-Glucan (BDG) uses ELISA to detect candidiasis. β D-Glucan level from BAL fluid is positive when the cut-off is p 130 pg / mL. This study aims to determine differences in the levels of Human 1,3β-D-Glucan from Bronchoalveolar Lavage (BAL) fluid between the immunocompromised and immunocompetent groups in patients with suspected lung cancer at RSU Dr. Saiful Anwar Malang.Method: A cross-sectional study was conducted on 33 lung cancer patients who had risk factors for invasive candidiasis in Dr. Saiful Anwar Hospital Malang.Result: 33 study patients had significant differences in BAL levels of Human 1,3β-D-Glucan in the immunocompromised and immunocompetent groups (p = 0.009). In the different tests, there was a slight difference in the levels of BAL Human 1,3β-D-Glucan but it was not statistically significant based on age and sex in the immunocompromised and immunocompetent groups (p = 0.632, p = 0.338, p = 0.472, p = 0.667).Conclusion: Patients suspected of lung cancer have risk factors for invasive candidiasis with higher BDG levels due to immunoparalysis. There were significant differences in the BAL Human levels of 1,3β-D-Glucan in the immunocompromised and immunocompetent groups.